Chicano Renaissance : Contemporary Cultural Trends - Herrera-Sobek, María; Ortiz, Isidro D., 1949-; Maciel, David (Book collections on Project MUSE., 2000)
Among the lasting legacies of the Chicano Movement is the cultural flowering that it inspired -- one that has steadily grown from the 1960s to the present. It encompasses all of the arts and continues to earn acclaim both nationally and internationally. Although this Chicano artistic renaissance received extensive scholarly attention in its initial phase, the post-Movimiento years since the late 1970s have been largely overlooked. This book meets that need, demonstrating that, despite the changes that have taken place in all areas of Chicana/o arts, a commitment to community revitalization continues to underlie artistic expression. This collection examines changes across a broad range of cultural forms -- including art, literature, music, television, radio, and cinema -- with an emphasis on the last two decades. Original articles by both established and emerging scholars review such subjects as the growth of Tejano music and the rise of Selena, how movies and television have affected the Chicana/o experience, the evolution of Chicana/o art over the last twenty years, and postmodern literary trends. Book jacket.